A review of pre-implantation genetic testing technologies and applications. Issue 1 (27th October 2022) - Du, Ren-Qian; Zhao, Ding-Ding; Kang, Kai; Wang, Fan; Xu, Rui-Xia; Chi, Chun-Li; Kong, Ling-Yin; Liang, Bo
Abstract : The first practice of pre-implantation genetic testing (PGT) was reported more than 30 years ago. PGT, originally named pre-implantation genetic screening (PGS) and pre-implantation genetic diagnosis (PGD), is now categorized as PGT for aneuploidies (PGT-A), PGT for monogenic/single-gene defects (PGT-M), and PGT for chromosomal structural rearrangements (PGT-SR). Patients with fertility issues caused by advanced maternal age, carrier status of chromosomal abnormalities, or harboring pathogenic variant(s) are recommended to undergo PGT to increase the possibility of successful live birth and avoid potentially affected newborns. High-throughput techniques, such as DNA microarrays and next-generation sequencing (NGS), have enabled comprehensive screening of all 24 chromosomes, instead of few loci at a time. Furthermore, as a comprehensive PGT, PGT-Plus was enabled by the rapid development of a genome-wide single-cell haplotyping technique to detect embryo aneuploidy, single-gene disorders, and chromosomal aberrations simultaneously using a single universal protocol. In addition, non-invasive approaches enable a more intact embryo during the biopsy procedure, which may avoid potential mosaicism issues at a certain scale by testing spent culture media (SCM). As a novel PGT application, PGT-P detects genome-wide variations in polygenic diseases, which account for a large proportion of premature human deaths and affect a markedly larger population than monogenic diseases, using polygenic risk score calculation to decrease the potential of affecting complex conditions. Owing to the emergence of new technologies recruited to PGTs, more couples with infertility issues have a promising chance of conceiving a healthy baby, ultimately facilitating the human species to live more prosper.